2022
DOI: 10.1001/jamainternmed.2022.0375
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antipsychotic Drug Exposure in Pregnancy With Risk of Neurodevelopmental Disorders

Abstract: IMPORTANCE Although antipsychotic drugs cross the placenta and animal data suggest potential neurotoxic effects, information regarding human neurodevelopmental teratogenicity is limited.OBJECTIVE To evaluate whether children prenatally exposed to antipsychotic medication are at an increased risk of neurodevelopmental disorders (NDD). DESIGN, SETTINGS, AND PARTICIPANTSThis birth cohort study used data from the Medicaid Analytic eXtract (MAX, 2000(MAX, -2014 and the IBM Health MarketScan Research Database (Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 48 publications
2
27
0
2
Order By: Relevance
“…Considering that some pregnant women will be exposed to antipsychotic(s), the guidelines mention that the use of antipsychotic drugs is relatively safe concerning the development of congenital malformations, pregnancy, and birth complications (Federatie Medisch Specialisten 2020a ). Furthermore, antipsychotics do not seem to increase the risk of neurodevelopmental disorders in offspring like Attention Deficit-Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) (Wang et al 2021 ; Straub et al 2022 ). Although the knowledge about the long-term effects of antipsychotics is limited, NVOG recommends continuing its use during pregnancy since the benefits of a well-treated psychotic disorder may outweigh its potential risk to the mother and fetus (Federatie Medisch Specialisten 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that some pregnant women will be exposed to antipsychotic(s), the guidelines mention that the use of antipsychotic drugs is relatively safe concerning the development of congenital malformations, pregnancy, and birth complications (Federatie Medisch Specialisten 2020a ). Furthermore, antipsychotics do not seem to increase the risk of neurodevelopmental disorders in offspring like Attention Deficit-Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) (Wang et al 2021 ; Straub et al 2022 ). Although the knowledge about the long-term effects of antipsychotics is limited, NVOG recommends continuing its use during pregnancy since the benefits of a well-treated psychotic disorder may outweigh its potential risk to the mother and fetus (Federatie Medisch Specialisten 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with previous findings of no increased risk of diagnosed neurodevelopmental disorders, learning disability, or poorer intelligence quotients among children prenatally exposed to antipsychotics. [11][12][13][14][15] However, some children with more severe neurodevelopmental disorders may attend special education schools and thus may not have participated in the test program. However, this selection was less likely to bias the present associations because there was no association between prenatal antipsychotic exposure and offspring's overall neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…10 Four recent studies demonstrated little or no increased long-term risks associated with prenatal antipsychotic exposure in neurodevelopmental disorders. [11][12][13][14] One study has evaluated potential cognitive outcomes, which may capture more subtle neurodevelopmental impairment. 15 To our knowledge, school performance, which is associated with cognitive ability, has not been investigated in this context so far.…”
mentioning
confidence: 99%
“…To the Editor There were 3 confounders not highlighted in the excellent study by Dr Straub and colleagues . First, their study was extensively controlled for multiple important confounders, including maternal age.…”
mentioning
confidence: 99%
“…A meta-analysis including 36 cohorts suggested that obesity was associated with increased risks for several neurodevelopmental outcomes, including ASD, ADHD, developmental delay, and emotional or behavioral problems . Hence, the study by Dr Straub and colleagues needed to control for these 3 confounding factors or address their omission in the study limitations …”
mentioning
confidence: 99%